2010
DOI: 10.5539/ies.v3n2p189
|View full text |Cite
|
Sign up to set email alerts
|

A research for identifying study anxiety sources among university students

Abstract: University students suffer to some levels of study anxiety, such as; have new experiences, environment and situation. Study anxiety is a real phenomenon. Campus environment has universal access to increase study anxiety among students. The prevalence of study anxiety has been acknowledged by students and educators. However, no current research exists to identify the study anxiety sources among university students. In this research, we present a survey aimed to identify of study anxiety sources among university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 10 publications
2
32
0
6
Order By: Relevance
“…A 40-item questionnaire with a five-point Likert-type Scale (1=never, 2=rarely, 3=sometimes, 4=often, and 5=always) was developed by the researcher after an extensive review of the literature on oral presentations (Morita, 2000;Elliott & Chong, 2004;Wolfe, 2008;Chuang, 2010;Vitasari, Abdul Wahab;Othman & Awang, 2010). It consisted of four sections: the first section described the demographic information of the sample, the second section consisted of 14 items and aimed to depict the participants' personal traits, the third section was set to find out about participants' presentation skills and consisted of 15 items, and the last section addressed the effect of audience and instructor on participants' oral presentations and consisted of 9 items.…”
Section: Students' Questionnairementioning
confidence: 99%
“…A 40-item questionnaire with a five-point Likert-type Scale (1=never, 2=rarely, 3=sometimes, 4=often, and 5=always) was developed by the researcher after an extensive review of the literature on oral presentations (Morita, 2000;Elliott & Chong, 2004;Wolfe, 2008;Chuang, 2010;Vitasari, Abdul Wahab;Othman & Awang, 2010). It consisted of four sections: the first section described the demographic information of the sample, the second section consisted of 14 items and aimed to depict the participants' personal traits, the third section was set to find out about participants' presentation skills and consisted of 15 items, and the last section addressed the effect of audience and instructor on participants' oral presentations and consisted of 9 items.…”
Section: Students' Questionnairementioning
confidence: 99%
“…Various studies have reported on the challenges faced by students in giving oral presentations (Ferris and Tagg, 1996;Weissberg;Tracy, 1997;Morita, 2000;King;Otoshi and Hefferman, 2008;Yang, 2010, Bankowski, 2010Chen, 2011;Noor Raha and Sarjit, 2011;Hafner & Miller, 2011;Mahani, et al (2014). This oral discourse is reported to be the most stressful communicative event as studies have indicated (Vitasari et al, 2010;Noor Raha & Sarjit, 2011;Suryani Sabri & Teah, 2014). The most difficult part is presenting in English especially for those less proficient students who eventually end up reading from the visuals.…”
Section: Challenges In Aopmentioning
confidence: 96%
“…They lack the confidence to speak to a live audience where they have to respond spontaneously to questions. (Morita, 2000;Woodrow, 2006;Vitasari et al, 2010;Noor Raha & Sarjit, 2011). Studies show how the students find it challenging to engage with the audience in discussions (Weissberg, 1993;Zappa-Hollman, 2007;Yang, 2010, Aguilar, 2004.…”
Section: Challenges In Aopmentioning
confidence: 99%
“…Para peneliti juga menemukan bahwa banyak hambatan saat proses pembelajaran, seperti kecemasan pada saat menghadapi ujian, kecemasan menghadapi pelajaran yang sulit, kecemasan berkomunikasi dan sosialisasi, serta kecemasan tentang keluarga dan kecemasan terhadap masalah di perpustakaan (Vitasari, 2010). Kecemasan adalah penyebab utama menurunnya prestasi akademik yang terjadi pada mahasiswa (Afolayan, 2013).…”
Section: Pendahuluanunclassified
“…Mahasiswa pada tingkat perguruan tinggi dapat dengan mudah mengalami kecemasan, khususnya pada saat proses pembelajaran, seperti kesulitan dalam mengikuti mata pelajaran tertentu, teman baru, krisis identitas, syok kultural dan masalah dalam pertemanan (Vitasari, 2010). Kecemasan dapat memiliki efek negatif, mahasiswa yang mengalami masalah kecemasan menunjukkan pencapaian akademik yang rendah, efikasi diri dan konsep diri yang kurang (Dobson, 2012).…”
Section: Pembahasanunclassified